RECONSTRUCTING THE PHILOSOPHY OF LOVE IN ISLAMIC EDUCATION: HUMANISTIC APPROACHES TO CULTIVATING EMPATHY, TOLERANCE, AND HARMONY - Wiwin Narti; Latifa Annum Dalimunthe; Al Amin (International Journal of Teaching and Learning, 2025)
This study aims to reconstruct the philosophy of love in Islamic education through a humanistic approach that integrates spirituality, empathy, and social harmony. Using a critical literature review and philosophical-hermeneutic analysis, the research explores classical Islamic thought, particularly the concepts of maḥabbah (love), ta’dib (ethical discipline), and rahmah (compassion), in relation to modern humanistic theories advanced by Carl Rogers and Abraham Maslow. The findings reveal that love in Islam functions not merely as an emotional state but as an epistemological and ethical foundation that unites divine knowledge with human experience. This reconstruction leads to the formulation of a Love-Based Islamic Humanistic Education (LIHE) model comprising three interrelated dimensions: spiritual foundation (cognitive-affective integration), pedagogical process (dialogical and empathic learning), and social manifestation (tolerance and harmony). The synthesis of Islamic and humanistic paradigms offers a transformative moral and character education framework, emphasizing empathy, inclusiveness, and ethical awareness. His study concludes that love should serve as the core of Islamic educational philosophy, bridging faith and humanity while addressing the challenges of pluralism, dehumanization, and moral disintegration in contemporary society. This research contributes theoretically by redefining the epistemology of Islamic education and practically by offering pedagogical guidelines for developing compassionate and inclusive Islamic learning environments.